Growth and Development of Young Karakul Sheep of Different Ethological Types - Khatamov A.Kh. (Zien Journals, 2023)
The article provides information on the growth and development indicators of different ethological types of black sheep, that is, the dynamics of live weight and the dynamics of exterior dimensions at different ages.
Keywords: karakalpak sur; karakul sheep; ethological type; live weight